The Influence of Transformational Leadership Style, Work Environment, and Job Satisfaction on Employee Performance in Manufacturing Companies - Suci Marwah; Ishma Noor Fadhilah; Lisa Harry Sulistiyowati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The purpose of this study is to examine how employee performance in manufacturing organizations is impacted by transformational leadership style, work environment, and job satisfaction. This study used an associative, quantitative methodology with a sample of 110 employees from PT. Siraj Badawi Cukup Rupiah. Likert scale surveys were used to gather data, and the Partial Least Squares-Structural Equation Modeling (PLS-SEM) approach was used to analyze the results. The findings of the study indicate that employee performance is not significantly impacted by transformative leadership. Employee performance is also not significantly impacted by the workplace. Nonetheless, employee performance is significantly impacted by work satisfaction. These results suggest that elements other than work environment and leadership style may be more important in raising employee performance. The significance of job happiness in raising employee commitment and productivity is emphasized by this study. Therefore, it is recommended that businesses concentrate more on enhancing job happiness in order to sustainably maximize employee performance.